2014
DOI: 10.1080/01635581.2014.956246
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Ellagitannins Isolated from Walnuts in Human Cancer Cells

Abstract: Walnuts contain many bioactive components that may slow cancer growth. A previous report showed that a diet supplemented with walnuts decreased the tumor size formed by MDA-MB-231 human cancer cells injected into nude mice. However, the mechanism of action was never determined. We characterized the effects of a methanol extract prepared from walnuts on human MDA-MB-231, MCF7, and HeLa cells. The extract was cytotoxic to all cancer cells. We identified compounds from the methanol extract that induced this cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…ETs are bioactive polyphenols that are abundant in some fruit herbs such as fructus chebulae, Phyllanthus emblica , and Punica granatum L . In contrast to the rather limited distribution of GTs in nature, ETs are typical constituents of many plant families, with more than 500 natural products characterized so far, such as davidiin, tellimagrandin I/II, vescalagin, and so on. ETs have previously been shown to exhibit in vitro and in vivo anticancer properties such as cell‐cycle arrest and apoptosis induction against various cancer cell lines, including liver, estrogen‐responsive breast, leukemia, and colon cancer cells, as well as inhibition of tumor formation and growth in animals.…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…ETs are bioactive polyphenols that are abundant in some fruit herbs such as fructus chebulae, Phyllanthus emblica , and Punica granatum L . In contrast to the rather limited distribution of GTs in nature, ETs are typical constituents of many plant families, with more than 500 natural products characterized so far, such as davidiin, tellimagrandin I/II, vescalagin, and so on. ETs have previously been shown to exhibit in vitro and in vivo anticancer properties such as cell‐cycle arrest and apoptosis induction against various cancer cell lines, including liver, estrogen‐responsive breast, leukemia, and colon cancer cells, as well as inhibition of tumor formation and growth in animals.…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…The results suggested that both antiproliferative and multigene regulatory action could be induced by ET‐modified miRNA expression in HepG2 cancer cells. Additionally, tellimagrandin I/II, belonging to ET family as the major compounds from methanol extract of walnuts, showed anticancer effects via impairment of mitochondrial function by decreasing intracellular pH and depolarizing mitochondrial membrane with release of cytochrome c as well as phosphatidylserine flipping . Interestingly, davidiin, which was isolated from P. capitatum extract, was investigated as a potential anticancer ET with the ability of inhibiting cancer cell growth via downregulating the enhancer of zeste homolog 2 (EZH2) and inducing apoptosis as well as suppressing tumor growth in xenograft models of Bel7404 .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…The BRB, for example, when evaluated by a non‐targeted metabolomic analysis showed over 4000 different UPLC peaks. [ 50 ] We chose to study BRBs based upon the anti‐cancer bioactivity of relevant phytochemicals in vitro [ 12–14,17,41,54,55 ] and accumulating studies of cancer preventive activity in rodent models. [ 16,19,40,47,56,57 ] Notably, due to the modest exposure of most populations to BRBs and the lack of specificity of berry intake on food frequency questionnaires, it is unlikely that epidemiological studies will provide insightful data regarding BRBs and cancer risk or other health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The pentagalloylglucose (1,2,3,4,6‐penta‐O‐galloyl‐beta‐ d ‐glucose), a pentagallic acid–glucose ester inhibits complex I, II, and III, but not complex IV, in a dose‐dependent manner and damages the mitochondrial membrane, causing reduction of ATP synthesis . Ellagitannins are another group of polygalloyl derivatives, which inhibit mitochondrial respiration associated with membrane damage, cytochrome c release, and subsequent apoptosis induction . PG has a different effect on mitochondrial respiration as it stimulates the respiratory oxygen uptake via oxidation of n ‐propanol obtained from PG degradation, whereas the gallic acid produced in the same reaction does not affect the oxygen consumption .…”
Section: Gallates Enhances Mitochondrial Respirationmentioning
confidence: 99%